Administration of Adenosine Triphosphate Provides Additional Value Over Programmed Electrophysiologic Study in Confirmation of Successful Ablation of Atrioventricular Accessory Pathways - Wei, Wei; Fang, Xianhong; Shehata, Michael; Wang, Xunzhang; Zhan, Xianzhang; Deng, Hai; Liao, Hongtao; Liao, Zili; Liu, Yang; Xue, Yumei; Wu, Shulin (Frontiers in Cardiovascular Medicine, 2021)
Objectives To study the additional value of adenosine triphosphate (ATP) in evaluation of ablation endpoint for accessory pathways (AP) over programmed electrophysiologic study (PES) alone and subsequent long term prognosis. Methods We reviewed consecutive patients with supraventricular tachycardias due to APs that underwent radiofrequency catheter ablation (RFCA) from Jan 2016 to Sept 2018 in our center. The patients were divided into two groups, the ATP group (who had passed both the ATP test and PES after ablation as the endpoint) and the non-ATP group (who had passed PES only after ablation as the endpoint). We reviewed the patients’ intra-cardiac electrograms and analyzed long-term outcomes. Results In total 1343 patients underwent RFCA. There were 215 patients in the ATP group with one lost to follow-up. There were 1128 patients in the non-ATP group with 39 lost to follow-up. Twenty-three patients in the ATP group demonstrated additional electrophysiological entities, including reappearance of the ablated APs in 16 patients, discovery of PES-undetected APs in 5, induction of atrial fibrillation in 5, premature atrial contractions in one and premature ventricular contractions in another. During 7 to 39 months (average 24.4 ± 9.5 months) follow-up, the recurrence rate was 8.41% (18/214) in the ATP group, 6.80% (74/1084) in the non-ATP group. In subjects with recurrence, 14 patients (14/18=77.8%) in the ATP group and 50 patients (50/74=67.6%) in the non-ATP group accepted redo ablations. Among the ATP-group, all the 14 redo APs were the old ones as before. Among the non-ATP-group, redo ablations confirmed that 39 APs were the old ones, while 20 APs were newly detected. Difference in recurrent AP locations confirmed by redo procedures between the two groups was significant (p=0.008). Existences of multiple APs in recurred cases were significantly higher than that in nonrecurred ones in the non-ATP group (p<0.001), while there was no such difference in the ATP group (p=0.114). Conclusions The existence of multiple APs is more common in recurrence cases if ATP were not used for confirmation of ablation endpoints. ATP probably adds additional value over PES alone by detecting weak AP conductions. ATP can evoke atrial and ventricular arrhythmias.